Sleep quality assessment in adolescents with and without Type 1 diabetes using the pittsburg sleep quality index - Fatma Ö Çömlek (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Many diseases, especially chronic diseases, can lead to sleep disturbances. Our study aimed to evaluate sleep characteristics and the relationship between sleep disorders and diabetes-related variables in type 1 diabetes adolescents and to compare these results with a non-diabetic group of similar age and gender. Methods: This cross-sectional study collected data from 40 healthy adolescents and 50 patients of the same age group with type 1 diabetes mellitus from January 2019 to June 2019. Subjects were asked to complete the Pittsburgh Uyku Kalitesi Anketi (PUKA). Patients who had nocturnal hypoglycemia in the preceding one month were excluded. Results: Total scores for PUKA were not significantly different between the two groups (P = 0.197). No significant relationship was found between sleep quality, duration of diabetes, and HbA1c levels in the diabetes group (P = 0.59, P = 0.41, respectively). Poor sleep quality (PUKA score ≥5) in girls without diabetes was higher (95% confidence interval: 1.26–11.61) than in the diabetes group (P = 0.031). Conclusion: In our study, the prevalence of sleep disorders in T1D patients was not higher than the non-diabetic population. However, the girls in the non-diabetic group had significant poor sleep quality. We hypothesize that this may be due to diabetes management bringing order and discipline to an adolescents life.